Micromechanistic study of textured multiphase polycrystals for resisting cold dwell fatigue - Zhang, Zhen (Acta materialia, 2018)
A micromechanical study has been conducted on low temperature dwell fatigue resistance in multiphase polycrystalline titanium alloys. The origin of the observed peak in strain rate sensitivity (SRS) over temperature has been explained by the transition from high-stress/low-temperature to low-stress/high-temperature thermally activated dislocation escape. The SRS peak is found to depend considerably on the rate sensitive slip systems in hexagonal close packed (HCP) α phase and body centered cubic (BCC) β phase in Ti alloys. This motivates the study of structural rate dependence, using the SRS peak, in commercially important textured multiphase Ti alloys. It is found that the SRS peak is dependent on texture and phase morphology in multiphase titanium alloys, which is different from some conventional binary alloys. A computational investigation of crystallographic texture shows that stronger rate sensitivity results from polycrystals with higher fractions of grains well-orientated for basal slip activation. This has also been demonstrated in independent experimental studies. Basketweave structures with multiple α variants have been shown to give the lowest SRSs over those with less variant and colony structures. In addition, the SRS peak, for representative textures and morphologies, has been found to be closely related to the creep behaviour in cold dwell fatigue. This understanding is important in microstructural design of titanium alloys for resisting cold dwell fatigue. [Display omitted]